2021
DOI: 10.1177/1096348021994194
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Crises and Impacts on Destinations: A Systematic Review of the Tourism and Hospitality Literature

Abstract: Tourism crises are important events affecting the development of destinations. However, the academic community lacks adequate knowledge from the accumulated literature on the classification attributes, spatial distribution, and impact structure of global tourism crises. This research analyzed 302 articles related to tourism crises from 1991 to 2020 drawn from the Social Sciences Citation Index database. Bibliometric and content analyses were conducted to identify the event types, regional distribution, impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 117 publications
(147 reference statements)
1
55
0
2
Order By: Relevance
“…The disruption in the global travel and tourism sectors caused by the COVID-19 pandemic has created significantly stressful situations for employees working in these sectors (Alonso et al, 2020), including the airlines. It has been demonstrated that external and global crises, such as economic recession, disease outbreaks and terrorist attacks, can greatly affect the hospitality and tourism industry as a whole (Duan et al, 2021). While an abundance of research has revealed the significance of IJCHM 34,10 organization-related events (e.g.…”
Section: Background Of Studymentioning
confidence: 99%
“…The disruption in the global travel and tourism sectors caused by the COVID-19 pandemic has created significantly stressful situations for employees working in these sectors (Alonso et al, 2020), including the airlines. It has been demonstrated that external and global crises, such as economic recession, disease outbreaks and terrorist attacks, can greatly affect the hospitality and tourism industry as a whole (Duan et al, 2021). While an abundance of research has revealed the significance of IJCHM 34,10 organization-related events (e.g.…”
Section: Background Of Studymentioning
confidence: 99%
“…Our theoretical research model underlines the importance of the spirit of youth adventure as a critical factor that generates new knowledge and develops young people’s work-related skills and general understanding of the job environment in the sector. The results relate to the HI system’s resilience from the socioeconomic perspective, affecting the macro-, meso-, and microlevels because of the impact on individuals, including the youth, businesses, communities, and nations [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 received the most scholarly attention. This attention may be attributed to the fact that articles on tourism crises are event-driven [17] and to the consequences and unprecedented impacts of COVID-19 on global tourism. In terms of geographical scope, the United Kingdom was the country with the most significant number of publications.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the outbreak of COVID-19 has drawn significant attention from tourism scholars across the world to understand the disastrous impacts on tourism [15,16]. This attention is probably due to the fact that the research on tourism crises is event-driven, which means the studies were often conducted promptly following the incidence of a particular crisis or disaster [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation